Answer:
So the other four items in total would cost $65.
Step-by-step explanation:
A juice shop has
different sizes of drinks. The regular-sized drink
is 1/3 of the super-sized drink. The mini-sized
the size of the regular-sized drink.
drink
is1/5
isof
of
• Into how many drinks would you divide a
super-sized drink to show? -
• Into how many drinks would you divide a
regular-sized drink to show?
• What fraction of the super-sized drink is the
mini-sized drink?
If the regular-sized drink is the same size as the super-sized drink, and the mini-sized drink is the same size as the regular-sized drink, then a super-sized drink can be divided into 2 regular-sized drinks or 4 mini-sized drinks.
What is division?Division is the process of splitting a number or an amount into equal parts. Division is one of the four basic operations of arithmetic, the ways that numbers are combined to make new numbers. The other operations are addition, subtraction, and multiplication.
here, we have,
we get the value:
Let's call the size of the mini-sized drink "M", the size of the regular-sized drink "R", and the size of the super-sized drink "S".
From the problem statement, we know that:
R = S (the regular-sized drink is the same size as the super-sized drink)
M = R (the mini-sized drink is the same size as the regular-sized drink)
To find out how many regular-sized drinks are in a super-sized drink, we can divide the size of the super-sized drink by the size of the regular-sized drink:
S / R = 1 (since R = S)
So a super-sized drink is equal to 1 regular-sized drink.
To find out how many mini-sized drinks are in a regular-sized drink, we can divide the size of the regular-sized drink by the size of the mini-sized drink:
R / M = 1 (since M = R)
So a regular-sized drink is equal to 1 mini-sized drink.
Therefore, a super-sized drink can be divided into 2 regular-sized drinks (since 1 super-sized drink = 2 regular-sized drinks) or 4 mini-sized drinks (since 1 super-sized drink = 2 regular-sized drinks = 4 mini-sized drinks).
learn more about division:
brainly.com/question/25289437
#SPJ9
93=30-e
This is 10 points I will give brainey
If you answer with the right answer the fastest no links are accepted
Answer:
93+30=123 so e equals 123
Step-by-step explanation:
To check, do 123-30=93
Please help me with this!
Answer:
root under 44 divide by 12
Step-by-step explanation:
we know that
cos= b/h
here,
b= TU
h= SU
p= ST
now,
cos= b/h
so,
cos= √(44) / 12
= 2 √(11) /12
= √(11) /6
hope it may help you
A binomial experiment has 4 trials in which p=0. 35. What is the probability of 1 success?.
Answer: 5798
Step-by-step explanation:
Probability of \(1\) success as per given condition is equals to \(0.384475\) ≈ \(0.4\).
What is probability?" Probability is defined as the ratio of number of favourable outcomes to the total number of outcomes.Probability is always less than or equals to one."
Formula used
For binomial experiment
Probability = \(^n C_r p^{r} q^{n-r}\)
\(p =\)success rate
\(q=\) failure rate
\(p+q=1\)
\(n=\)Number of trials
\(r=\) number of success
According to the question,
Total number of trials \('n' =4\)
Number of success \('r' =1\)
\(p = 0.35\\\\q = 1-0.35\\ \\\implies q = 0.65\)
Substitute the value to get the required probability,
Probability \(= ^4C_1 (0.35)^{1}(0.65)^{4-1}\)
\(=\frac{4!}{(4-1)!1!} \times\frac{35}{100}\times(\frac{65}{100})^{3} \\\\= 4 \times \frac{35}{100}\times \frac{274625}{1000000} \\\\= 0.384475\)
≈ \(0.4\)
Hence, probability of \(1\) success as per given condition is equals to \(0.384475\) ≈ \(0.4\).
Learn more about probability here
brainly.com/question/11234923
#SPJ2
Choose the correct option:
The power of a test is
A) the probability of rejecting a true null hypothesis.
B) one minus the probability of not rejecting a false null hypothesis.
C) Type II error.
D) Type I error.
The correct option is B) one minus the probability of not rejecting a false null hypothesis.
The power of a statistical test refers to its ability to correctly reject a false null hypothesis. It is the probability of rejecting a false null hypothesis, or in other words, the probability of correctly concluding that there is an effect or difference when one truly exists.
Option A) "the probability of rejecting a true null hypothesis" is incorrect because the power of a test is not related to the probability of rejecting a true null hypothesis. The power is focused on the ability to detect false null hypotheses.
Option C) "Type II error" is incorrect because Type II error refers to failing to reject a false null hypothesis. It is the error of accepting a false null hypothesis or failing to detect an effect or difference when one truly exists.
Option D) "Type I error" is also incorrect because Type I error refers to rejecting a true null hypothesis, which is not directly related to the power of a test.
Therefore, the correct option is B) one minus the probability of not rejecting a false null hypothesis, which represents the power of a test.
Learn more about probability here:
https://brainly.com/question/31828911
#SPJ11
How to divide 49 yd in the ratio 1:6?
Answer:
7:42
Step-by-step explanation:
First off you add the ratio together-
6+1=7
Then you divide-
49÷7= 7
7 is equal to 1 in this ratio.
To write out the ratio you need to multiplicate-
7×1=7
and
6×7= 42
Leaving the as-
7:42
Answer:
7:42
Step-by-step explanation:
First, add up the two numbers in the ratio to get 49.
Next, divide the total amount by 49, i.e. divide £16 by 8 to get £5. £5 is the amount of each 'unit' in the ratio.
Then you need to divide the total amount using that number i.e. 49/16 = 7/42.
To work out how much each person gets, you then multiply their share by the ratios. Therefore, the answer is 7 yd and 42 yds.
Math help please due soon thanks
Answer with step-by-step explanation:
I'll use the list of referents you had on your other question and I believe this is a reference to that list.
Part A:
Use the reference of an adult stride (about 1 yard) to estimate the dimensions and length of the lawn edging. The dimensions can be used to find the area, in square yards, that is required to fill both sides of the flower beds.
Part B:
Similarly, you can use an adult stride of about 1 yard as a reference to measure to dimensions of the paved area and the dimensions of the brick. Using these dimensions, you can find area of the paved walkway and the area (surface area of top only) in square yards. Use these areas to find the approximate number of bricks needed to fill the walkway.
Find the distance CD rounded
to the nearest tenth.
C = (4,7) D= (7,11)
CD= [?]
HINT: Use the distance formula:
d = √(x₂-x₁)² + (Y2 − 1)²
Enter
√(x₂-x₁)² + (Y2 − 1)²
√(7-4)² + (11− 7)²
√(3)² + (4)²
√(9)+ (16)
√(25) = 5
Thus, CD = 5
Hope this helps!
The perimeter of the figure below is 40 cm. what is the length of the side labelled ‘x’?
Answer:
13.72 cm
Step-by-step explanation:
Perimeter of the given figure = sum of all sides
40 = x + 9.7 + 16.58
40 = x + 26.28
x = 40 - 26.28
x = 13.72 cm
What is the sale price on a pair of jeans that was originally priced at $29.95 if tHe discount waS 20%?
My answer is too short
The answer is $5.99
The sale price on a pair of jeans is 23.96 dollar.
What is the fundamental principle of multiplication?Multiplication is the mathematical operation that is used to determine the product of two or more numbers. If an event can occur in m different ways and if following it, a second event can occur in n different ways, then the two events in succession can occur in m × n different ways.
We are given that shop advertises pair of jeans that was originally priced at $29.95 if tHe discount waS 20%
Here 20 percent is equivalent to 1/5
So,X=(20× 29.95)÷100
x = 5.99
the sale price is
29.95 - 5.99
= 23.96 dollar.
Learn more about multiplications;
brainly.com/question/14059007
#SPJ2
NEED THIS ASAP HELPPP
Answer:
Step-by-step explanation:
The answer is D 28 degrees
20. Given the area, find the side length.
Answer:
Step-by-step explanation:
Area of a square = 49a⁸b¹⁰
Side = √49a⁸b¹⁰
= √7²*(a⁴)²*(b⁵)²
= (7a⁴b⁵)²
Side = 7a⁴b⁵
Hey I need help on this question thanks Love ya'll so much!
Answer:
Madeline picks 6 pieces of fruit per hour
Step-by-step explanation:
divide total amount of fruit she picked on that day by the amount of hours she spent picking
12/2 = 6
42/7 = 6
if demand is 106 during january, 120 in february, 134 in march, and 142 in april, what is the 3-month simple moving average for may? answer 132 126 138 i don't know yet
The 3-month simple moving average for May is 132.
To calculate the 3-month simple moving average for May, we need to take the average of the demand values for the three preceding months (February, March, and April).
The demand values for these months are 120, 134, and 142, respectively. To find the moving average, we sum these values and divide by 3 (the number of months):
Moving Average = (120 + 134 + 142) / 3 = 396 / 3 = 132
Therefore, the 3-month simple moving average for May is 132.
The simple moving average is a commonly used method to smooth out fluctuations in data and provide a clearer trend over a specific time period. It helps in identifying the overall direction of demand changes. By calculating the moving average, we can observe that the average demand over the past three months is 132 units. This provides an indication of the demand trend leading up to May. It's important to note that the moving average is a lagging indicator, as it relies on past data to calculate the average.
Learn more about moving average
https://brainly.com/question/29099714
#SPJ11
(1, 3), m= -3/4
What’s the point slope?
Find the characteristic polynomial, eigenvalues, and a basis for the eigenspace associated with each eigenvalue for the matrix 1 0 0 A= -25 -2 -24 -1
We need to find the characteristic polynomial, eigenvalues, and a basis for the eigenspace associated with each eigenvalue for the given matrix A.
To find the characteristic polynomial, we first need to find the determinant of the matrix (A - λI), where I is the identity matrix and λ is the eigenvalue. We have:
|\(\left[\begin{array}{ccc}1-\lambda&0&0\\-25&-2\-\lambda&24\\0&0&-1-\lambda\end{array}\right]\)
Expanding along the first row, we get:(1-λ)[(-2-λ)(-1-λ) - 0] - 0 - 0 = (1-λ)(λ^2 + 3λ + 2) = (1-λ)(λ+1)(λ+2). So the characteristic polynomial is (1-λ)(λ+1)(λ+2). To find the eigenvalues, we set the characteristic polynomial equal to zero and solve for λ. We get λ = 1, λ = -1, and λ = -2. Next, we need to find the eigenvectors for each eigenvalue. We first consider λ = 1. To find the eigenvectors, we need to solve the system of equations (A - λI)x = 0, which in this case is:
\(\left[\begin{array}{ccc}0&0&0\\-25&-3&24\\0&0&0\end{array}\right]\)
Solving this system, we get x1 = 0 and x2 = -8x3. So the eigenvectors associated with λ = 1 are of the form [0, -8t, t], where t is any nonzero real number. A basis for this eigenspace is {[0, -8, 1]T}. Similarly, for λ = -1, we get a basis for the eigenspace as {[0, -4, 1]T}. For λ = -2, we get a basis for the eigenspace as {[0, 0, 1]T}.So the characteristic polynomial is (1-λ)(λ+1)(λ+2), the eigenvalues are λ = 1, λ = -1, and λ = -2, and the corresponding eigenspaces have bases {[0, -8, 1]T}, {[0, -4, 1]T}, and {[0, 0, 1]T}, respectively.
Learn more about eigenspace here:
https://brainly.com/question/28564799
#SPJ11
Given that {x, x3} is a fundamental set of solutions of x2y’’ -3xy’ + 3y = 0, find the general solution of x2y’’ + 3xy’ + 3xy = 4x7
Thus, the general solution is y(x) = -x + 2x^3 + c₁x + c₂x^3.
To find the general solution of the differential equation x^2y'' + 3xy' + 3xy = 4x^7, we can use the method of variation of parameters.
Given that {x, x^3} is a fundamental set of solutions of the homogeneous equation x^2y'' - 3xy' + 3y = 0, we can use these solutions to find the particular solution.
Let's assume the particular solution has the form y_p = u(x)x + v(x)x^3, where u(x) and v(x) are unknown functions.
Differentiating y_p:
y_p' = u'x + u + v'x^3 + 3v(x)x^2
Differentiating again:
y_p'' = u''x + 2u' + v''x^3 + 6v'x^2 + 6v(x)x
Substituting these derivatives into the original differential equation, we have:
x^2(u''x + 2u' + v''x^3 + 6v'x^2 + 6v(x)x) + 3x(u'x + u + v'x^3 + 3v(x)x^2) + 3x(u(x)x + v(x)x^3) = 4x^7
Simplifying and grouping like terms:
x^3(u'' + 3v') + x^2(2u' + 3v'' + 3v) + x(u + 3v' + 3v) + (2u + v) = 4x^5
Setting the coefficients of each power of x to zero, we get the following system of equations:
x^3: u'' + 3v' = 0
x^2: 2u' + 3v'' + 3v = 0
x^1: u + 3v' + 3v = 0
x^0: 2u + v = 4
Solving this system of equations, we find:
u = -1
v = 2
Therefore, the particular solution is y_p = -x + 2x^3.
The general solution of the differential equation x^2y'' + 3xy' + 3xy = 4x^7 is given by the sum of the particular solution and the homogeneous solutions:
y(x) = y_p + c₁x + c₂x^3
where c₁ and c₂ are arbitrary constants.
To know more about general solution,
https://brainly.com/question/31384627
#SPJ11
Mrs Smith walks a half a mile a day after work. She works five days a week. How many yards will she have walked for the week by Friday morning?
The distance Mrs. Smith covers is 3520 yards during the duration of the week by Friday morning.
One week has seven days in total.
Mrs. Smith walks half a mile each day after work, she walks a total of
0.5 miles/ day × 7 days/ week = 3.5 miles/ week
Now, if we calculate the distance on Friday morning, she must have walked four times till Friday morning since she has to walk after her work.
Therefore,
0.5 miles/ day × 4 days = 2 miles
To convert miles to yards, we can use the fact that there are 1760 yards in one mile:
2 miles/week × 1760 yards/mile = 3520 yards/week
Therefore, by Friday morning, Mrs. Smith will have walked 3520 yards.
To learn more about the distance at
https://brainly.com/question/26264531
#SPJ4
Find a vector of length 2 in the opposite direction to v.
To find a vector of length 2 in the opposite direction to vector v, we need to negate the direction of v and then scale it to have a length of 2.
Let's assume vector v is represented as v = (v1, v2, v3, ..., vn) in n-dimensional space.
To negate the direction of v, we simply multiply each component of v by -1, resulting in the vector -v = (-v1, -v2, -v3, ..., -vn).
Next, we need to scale -v to have a length of 2. We can achieve this by multiplying each component of -v by a scalar factor. Let's denote this scalar factor as k.
Therefore, our goal is to find k such that ||k(-v)|| = 2, where ||.|| represents the length or magnitude of a vector.
Using the Euclidean norm, we have:
||k(-v)|| = sqrt((k(-v1))^2 + (k(-v2))^2 + ... + (k(-vn))^2)
Squaring both sides to eliminate the square root:
(k(-v1))^2 + (k(-v2))^2 + ... + (k(-vn))^2 = 4
Expanding the equation:
k^2(v1^2 + v2^2 + ... + vn^2) = 4
Simplifying:
k^2 ||v||^2 = 4
k^2 = 4 / ||v||^2
Taking the square root of both sides:
k = ±2 / ||v||
Now we have the scalar factor k. To obtain the vector of length 2 in the opposite direction to v, we multiply -v by this scalar:
(-v) * (±2 / ||v||) = (-v1 * (±2 / ||v||), -v2 * (±2 / ||v||), ..., -vn * (±2 / ||v||))
This resulting vector will have a length of 2 and will point in the opposite direction to v.
Learn more about vector
brainly.com/question/24256726
#SPJ11
Let limx→0x2[x]2=l and limx→0x2[x2]=m where [.] denotes greatest integer.Then,
To find the values of "l" and "m" in the given limits, we need to determine the limits of the expressions as x approaches 0.
For the first limit, limₓ→0 x²[x]² = l, where [.] denotes the greatest integer function.
To evaluate this limit, we consider the values of x as it approaches 0 from both the positive and negative sides. Since the greatest integer function rounds down to the nearest integer, [x]² will always be 0 for any non-zero value of x. Therefore, as x approaches 0, x²[x]² will also approach 0.
Hence, l = 0.
For the second limit, limₓ→0 x²[x²] = m, where [.] denotes the greatest integer function.
Again, we consider the values of x as it approaches 0 from both the positive and negative sides. For positive values of x, [x²] will be equal to x² since x² is always an integer. However, for negative values of x, [x²] will be equal to (x² - 1) because it rounds down to the nearest integer less than x².
So, as x approaches 0, x²[x²] will approach 0 on the positive side but approach -1 on the negative side.
Therefore, m = 0 on the positive side, and m = -1 on the negative side.
In conclusion:
l = 0
m = 0 for positive values of x, and m = -1 for negative values of x.
To know more about Integer visit-
brainly.com/question/490943
#SPJ11
What is the slope of y=20x+50 and what dose it represent
PLEASEE HELPP!!!! ASAPP PLEASE PLEASEE!!!
On a coordinate plane, point E is (negative 6, 8), point A is (5, 7), point B is (10, negative 2), point C is (8, negative 6), point D is negative 6, negative 6).
Which statements are true? Select all that apply
The length of side ED is equal to the length of side DC.
The length of side EA is equal to the length of side AB.
You can find the length of side BC by counting.
Shape ABCDE is a pentagon.
Shape ABCDE is a hexagon.
Answer:
two are correct: side ED is equal to DC, and ABCDE is a pentagon
Step-by-step explanation:
pentagon is a polygon having 5 sides
You can find the length of BC by using the distance formula
Answer:
a, d to make it simpler
Step-by-step explanation:
Which of the following has a value less than or equal to 5 1/4
1. 0.52 x 10
2. 12 x 1/2
3. -0.2 x -23
Answer:
1 and 3
Step-by-step explanation:
Ok so you need to start with solving each answer.
1. 5.20
2. 6
3. 4.6
so actually. 1 and 3 have a value less than or equal to 5 1/4 or 5.25
The ratio of three numbers are 4:5:3. The sum of the numbers is 84. What are the 3 numbers?
Answer:
if 4:5:3=84 you start by adding (4+5+3=9)....so 9 equals to 84 what about (4) cross multiply....you will 4=28 .....if 9 =84 what about 5 cross multiply.....you will get 35....if 9 =84 what about 3
cross multiply.....you will get 21 so the numbers are.
4=38
5=35
3=21
I NEED HELP!!! This is due tonight and I need help solving
Answer:
x = 2\(\sqrt{5} \)
Step-by-step explanation:
Okay first you need to find the side of the other triangle (the side that also is a hypotenuse for the other triangle).
So we can use pythagorean's theorum
\(a^{2} +b^{2} =c^{2} \) with c being the hypotenuse
\(a^{2} +2^{2} =7^{2} \)
a^2 + 4 = 49 subtract 4 from both sides
a^2 = 45 then do the sqaure root
a = \(\sqrt{45} \) which can be simplified to 3\(\sqrt{5} \)
so... 3\(\sqrt{5} \) or \(\sqrt{45} \) is our hypotenuse for the other triangle
\(5^{2} +b^{2} = \sqrt{45} ^{2} \)
25 + b^2 = 45 subtract 25 from both sides
b^2 = 20 then do the square root
b (or x in this problem) = \(\sqrt{20} \)
or when simplified, 2\(\sqrt{5} \)
Find the side indicated by the variable. Round to the nearest tenth.
PLEASE HELP
Answer:
I think it would be 10.1 but I'm not 100% sure
Helppppp_____________
Answer:
\( {8}^{ \frac{x}{3} } \)
Step-by-step explanation:
Hope that this is helpful.
Have a great day.
what fraction of the whole garden is yellow bean plants?
Answer: :( 4/12
Step-by-step explanation: 75 % sure :( :(
answer:
first we multiply the 2 fractions together to get the fraction of yellow beans in the garden, then simplify the fraction
3/4×1/3=3/12=1/4
Rent expense in Volusia Company's 2014 income statement is $420,000. If Prepaid Rent was $70,000 at December 31, 2013, and is $95,000 at December 31, 2014, the cash paid for rent during 2014 is:A. $480,000B. $445,000C. $395,000D. $420,000
As per the mentioned informations, the cash paid for rent during 2014 is calculated to be $395,000. So, the correct answer is option (C) i.e. $395,000.
To calculate the cash paid for rent during 2014, we need to use the information given in the problem and apply the following formula:
Cash paid for rent = Rent expense + Prepaid rent at the beginning of the period - Prepaid rent at the end of the period
Substituting the values given in the problem, we get:
Cash paid for rent = $420,000 + $70,000 - $95,000
Cash paid for rent = $395,000
Therefore, it can be concluded that the correct answer is (C) $395,000.
Learn more about Cash :
https://brainly.com/question/13226199
#SPJ4
Write each polynomial in standard form. Identify the leading coefficient.
4x + 2x5 – 6x3 + 2
Given:
The polynomial is
\(4x+2x^5-6x^3+2\)
To find:
The standard form of the polynomial and leading coefficient.
Solution:
In standard form of a polynomial, we arrange the terms in descending order of their degrees.
Leading coefficient is the constant value before the variable with highest power.
Let the given polynomial be p(x).
\(p(x)=4x+2x^5-6x^3+2\)
The standard form of the polynomial is
\(p(x)=2x^5-6x^3+4x+2\)
The highest power of x is 5 and 2 is before \(x^5\). The leading coefficient is 2.
Therefore, the standard form of the polynomial is \(2x^5-6x^3+4x+2\) and the leading coefficient is 2.